Study on characteristics of sediment and bed load discharge in Sungai Jemberau at Tasik Chini - Nadiatul Adilah, Ahmad Abdul Ghani; Siti Nur Marhidayu, Mohamad Sukri (IOP Publishing, 2019)
This study had been carried out to identify sediment characteristics in Sungai Jemberau at Tasik Chini, and to compare their bed load dischargedata between the measured and predicted methods. It was observed that extensive uncontrolled mining activities nearby Sungai Jemberau had led to erosion and hence increasing bedload discharge. This situation hadbecome worst during storm or rainfall events because of increased sedimentation process.The river depth hadbecome shallow as the river bed was filled with bedload settles on the riverbed. Due to this situation, flooding becomes more severe as the river overflows. From here, the bedload discharge can be estimated using the DuBoys and Schoklitsch equation. Sediment size was classified using the Udden Wentworth Scale. Mostly, the median grain size (